Dynamic Information Disclosure - Dierker, Martin; Subrahmanyam, Avanidhar (Contemporary Accounting Research, 2017)
Abstract We explore the optimal timing of voluntary disclosures when firms and outside investors have correlated but not identical signals. By delaying disclosure of their signal, firms encourage the acquisition of information by investors by reducing the latter's exposure to the long‐term risk of holding the asset. Immediate disclosure reduces rents from acquiring the correlated signal, and thus is sometimes suboptimal in a dynamic setting. We characterize conditions under which postponing disclosure is preferable, which allows us to develop predictions on the timing of voluntary information disclosures such as management guidance.